Inhibisi Lipase Pankreas secara In Vitro oleh Ekstrak Air dan Etanol Daun Asam Jawa (Tamarindus indica) dan Rimpang Kunci Pepet (Kaempferiae rotundae) - Pradono, Dyah Iswantini; Darusman, Latifah Kosim; Susanti, Ai (Jurnal Natur Indonesia, 2011)
Tamarind and kunci pepet has been used traditionally as herbal medicine to reduce body weight or used asantiobesity. But the mechanism in vitro of this herbal in reducing body weight has not been known yet. Theobjective of this research is to evaluate these herbal as antiobesity by their water and ethanol extracts capabilityin inhibiting pancreatic lipase activity in vitro at pH 8, incubation time 45 minutes, and temperature 400C. Pancreaticlipase used in this research was human pancreatic lipase with concentration of 1.4 × 10-5 μg/μl and the substratewas sesame oil with concentration of 16.2 μg/μl. The water and ethanol extracts of tamarind leaves containedalkaloids, flavonoids, saponins, steroids, and tannins. Water extract of kunci pepet contained alkaloids, flavonoids,saponins, and tannins, while ethanol extract contained alkaloids, flavonoids, saponins, and triterpenoids. Theresults of tamarind leaves extracts showed that ethanol extract in concentration of 150 ppm had the highestinhibitory effect, with the value of 49.0%. Water extract of kunci pepet at concentration of 200 ppm had the highestinhibition, with the value of 65.1%. These values were higher than inhibitory effect of Xenical® 100 ppm as thepositive control, with the inhibition value of 10.6%.